Low Serum Zinc Levels as a Risk Factor for Tuberculosis Coinfection in Patients with Human Immunodeficiency Virus - Rionaldo Anthonius de Quelyoe Junior; Anak Agung Ayu Yuli Gayatri; I Ketut Agus Somia (PT Dexa Medica, 2026)
Background: Tuberculosis (TB) remains the leading opportunistic infection and cause of mortality among people living with human immunodeficiency virus (HIV). Micronutrient deficiencies, particularly zinc deficiency, have been implicated in immune dysfunction and increased susceptibili.ty to TB. However, data regarding the role of serum zinc levels in HIVTB coinfection in Indonesia remain limited. Objective: To evaluate low serum zinc levels as a risk factor for tuberculosis infection among HIV-infected patients. Methods: This was a nested case-control study conducted at RSUP Prof. dr. I.G.N.G. Ngoerah, Denpasar, Bali, Indonesia, between May and October 2024. A total of 60 adult HIV patients wereenrolled, consisting of 30 HIV-TB coinfected patients (cases) and 30 HIV patients without TB (controls), matched by age and sex. Serum zinc levels were measured using inductively coupled plasma-mass spectrometry (ICP-MS). Tuberculosisdiagnosis was established using the GeneXpert MTB/RIF molecular assay. Bivariate and multivariate logistic regression analyses were performed to identify independent risk factors for TB coinfection. Results: Low serum zinc levels(<70 mcg/dl) were significantly more frequent among HIV-TB patients compared to controls (76.7% vs. 30.0%). Multivariate logistic regression showed that zinc deficiency was independently associated with TB coinfection (adjusted odds ratio [aOR] 5.56; 95% confidence interval [CI] 1.431–21.590; p=0.013). Other variables, including lack of isoniazid (INH) preventive therapy and CD4 count <200 cells/μl (aOR 2.64; 95% CI 0.54–12.98; p=0.223), were not independently associated with TB coinfection. Conclusion: Low serum zinc levels are an independent clinical risk factor for tuberculosisamong patients with HIV. Assessment of zinc status may help identify HIV-infected individuals at higher risk for TB and support targeted preventive strategies.